Honest - Jonsson, Ulrika (London Sidwick & Jackson, 2002)
This is Ulrika making sense of her life in a frank and moving autobiography.
Include Illustration and Index
Keywords: Television Personalities -- Women Television Personalities -- Great Britain -- Jonsson, Ulrika, 1967-